2012 Proceedings Annual Reliability and Maintainability Symposium 2012
DOI: 10.1109/rams.2012.6175474
|View full text |Cite
|
Sign up to set email alerts
|

Launch vehicle reliability growth

Abstract: This paper addresses the importance of considering the initial reliability and reliability growth as opposed to only the mature risk estimate when making relative comparisons among developmental launch vehicle (LV) alternatives and introduces the current model used to perform this type of analysis.Probabilistic risk assessments (PRA) often focus on modeling the mature state of a system under consideration; however, in the aerospace field of LV design such an assessment can be dangerously misleading. Due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Vehicles based on existing and mature technologies and design elements should experience a much quicker growth in reliability as only the integration aspects of the system are unknown. However, launchers based on immature technologies and designs will experience slower growth in reliability and may present a greater risk during early flights even if the projected reliability at maturity is higher 21) .…”
Section: Future Launch Vehiclesmentioning
confidence: 99%
“…Vehicles based on existing and mature technologies and design elements should experience a much quicker growth in reliability as only the integration aspects of the system are unknown. However, launchers based on immature technologies and designs will experience slower growth in reliability and may present a greater risk during early flights even if the projected reliability at maturity is higher 21) .…”
Section: Future Launch Vehiclesmentioning
confidence: 99%
“…Ares V ascent failure probability was adapted from Ares I risk assessments. Commercial launcher failure risk was based on heritage data [6]. Delivery risks stemmed from complex, temporally sensitive mission operations such as rendezvous and docking, on-orbit fuel transfer, and solar array deployments, and are also heritagebased.…”
Section: Demand-based Risksmentioning
confidence: 99%
“…This can be explained by the fundamental difference in modeling approach between a bottom-up and top-down PRA methodology: bottom-up approaches contain only component-originated failures, while top-down approaches also contain failures stemming from unintended subsystem interactions with the environment, other subsystems, and within the overall subsystem. All of these interactions could be considered as design defects, as they are potentially knowable interactions; as processing defects, which are somewhat unavoidable; or as unknown-unknown type defects, which may be completely unavoidable [8]. It has been shown that these types of defect-originated failures are dominant in the risk of complex, single-use space systems [9].…”
Section: Propulsion Subsystem Failure Probabilitiesmentioning
confidence: 99%
“…These include two traditional PRA methodologies [3,4], an innovative approach [5], and a top-down approach [6], all of which are explored by using the propulsion subsystem of the Lunar Reconnaissance Orbiter (LRO) as a comparative basis for the methodologies considered [7]. Similarities, differences, benefits, and drawbacks of various bottom-up, componentbased PRA approaches and the top-down approach are elucidated in terms of the process of modeling a system, the actionable information produced for the design team, and the overall quantitative risk evaluation of the system as compared to similar heritage space systems.Results of the various PRA methodologies are examined at the level of component failure rates, single-component failure probabilities, single-function failure probabilities where redundancy exists in the design, as well as the subsystem failure probability for the nominal LRO mission.Ultimately, all of the bottom-up, component-based PRA methods capture only the risk of a mature system and miss the risk contribution of design defects, which have been shown to be key drivers of reliability in single-use developmental systems [8,9]. Therefore, further steps must be taken to incorporate this contribution in future PRA methodologies.…”
mentioning
confidence: 99%
See 1 more Smart Citation